Nitrogen doses on development of tall seedlings of yellow passion-fruit - Almeida Bertani, Rosemary Marques de; Silva, Sueellen Pereira da [UNESP]; Fernandes Deus, Angelica Cristina [UNESP]; Antunes, Andrea Maria; Fischer, Ivan Herman (Univ Estadual Mato Grosso Sul, 2019)
Due to Cowpea aphid-borne mosaic virus dissemination, therefore it is necessary to produce larger and more vigorous seedlings and, currently, there is a lack of information about the nutritional aspects in the formation of these seedlings with quality. This study aimed to evaluate the nitrogen doses (N) applied on side-dressing on development of tall seedlings of yellow passion-fruit. The experimental design was a randomized block, with five treatments and five replications. The treatments consisted of five N levels (0; 0.17; 0.34; 0.51 and 0.68 g L-1) as calcium nitrate, applied on side-dressing in the form of nutrient solution, weekly until 90 days after emergence. Nitrogen rates from 0.34, 0.51 and 0.68 g L-1 increased the N content in the leaves, providing further development in height, stem diameter and leaf area. The rate of 0.34 g L-1 of N may be indicated in the tall seedlings production, because reached height, diameter, green index, and leaf area formation very close to the maximum rate of 0.68 g L-1 N and average higher the rate of 0.51 g L-1 N, however, field studies are needed to validate. The concentrations (g kg(-1)) in leaves at a rate of 0.34 g L-1 of N were: N (21), P (0.86), Mg (2.58), B (29.6), these values are suitable for tall seedlings confirmed by the observed rates.
Keywords: Passiflora edulis; mineral nutrition; green index